Determinants of housing price in Singapore - Lau, Xue Kei; Law, Jin Yao; Lee, Wei Ying; Liew, Wei Xiang; Tan, Boon Suan (2022)
The main purpose of this study is to examine the determinants of housing price in Singapore. The increasing housing price level in Singapore over the years has become one of the alarming issues discussed nowadays. Therefore, this study attempts to investigate the relationship between housing price and macroeconomic determinants which include gross domestic product, inflation rate, unemployment rate, money supply, and foreign exchange rate in Singapore from 2005 quarter 1 to 2020 quarter 4. The ARDL bounds testing to cointegration, and Granger Causality test procedures are employed in the empirical part of this study. In general, the empirical results show that unemployment rate and foreign exchange rate possess a significant positive relationship towards Singapore’s housing price, whereas money supply possesses a significant negative relationship towards Singapore’s housing price. On the other hand, it is discovered that gross domestic product and inflation rate have no significant impact on Singapore’s housing price. Based on the results, it is concluded that money supply possesses the greatest influence on Singapore’s housing price among the five determinants.